Extractive Spectrophotometric Determination of Pioglitazone Hydrochloride Using Both Acidic and Basic Dyes - Gowri Sankar, D.; Rajendra Kumar, J.M.; Reddy, M.V.V.N. (Asian Journal of Chemistry, 2010)
Four simple extractive spectrophotometric methods have been developed for the estimation of Pioglitazone hydrochloride in pure and pharmaceutical dosage forms. These methods are based on the formation of ion association complexes of the drug with tropaeolin-OOO or woolfast blue or saffranin-O or methylene blue; the complexes were extracted with chloroform and the absorbances of the chloroform layer were measured at 487 nm, 590 nm, 520 nm and 650 nm respectively. These methods have been statistically evaluated and are found to be precise and accurate.